2021
DOI: 10.1139/cjes-2020-0075
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and sedimentology of the Pennsylvanian Grande Anse Formation, Cumberland Basin, eastern Canada: its relationship to salt tectonics and coeval strata of the Joggins World Heritage Site

Abstract: The Cumberland Basin is one of several sedimentary basins comprising the late Paleozoic Maritimes Basin complex of eastern Canada. Pennsylvanian salt tectonics in the Cumberland Basin caused two salt mini-basins to evolve either side of the Minudie Anticline, a salt wall. South of the wall (Athol Syncline), along the Joggins World Heritage shoreline, an ~ 3000 m succession of strata (Little River, Joggins, Springhill Mines, and Ragged Reef formations) accumulated conformably on the Boss Point Formation. North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Previous sedimentological and geochemical studies of the Grande Anse Formation (Allen et al ., 2013; Bahr & Keighley, 2021, 2022) have all supported the interpretation of sedimentation in a tropical, semi‐humid to humid, terrestrial climate. Suttner & Dutta (1986) also developed a bivariate log/log plot of selected detrital components that can assess point‐count data to infer palaeoclimate.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Previous sedimentological and geochemical studies of the Grande Anse Formation (Allen et al ., 2013; Bahr & Keighley, 2021, 2022) have all supported the interpretation of sedimentation in a tropical, semi‐humid to humid, terrestrial climate. Suttner & Dutta (1986) also developed a bivariate log/log plot of selected detrital components that can assess point‐count data to infer palaeoclimate.…”
Section: Discussionmentioning
confidence: 74%
“…This stratigraphy collectively comprises >3 km of strata that are disconformable on the Mabou Group (Calder et al ., 2005; Waldron et al ., 2013; Craggs et al ., 2017). A series of biostratigraphic (Utting et al ., 2010), sedimentological and geochemical studies (Bahr & Keighley, 2021, 2022), have also demonstrated that the overlying >900 m thick strata south of the Anticline, previously described as the Ragged Reef Formation by Ryan et al . (1991), has many similarities to the Grande Anse Formation north of Minudie Anticline, which was first mapped by Norman (1941).…”
Section: Geological Contextmentioning
confidence: 89%
See 3 more Smart Citations